The Utilization of Picture Media in Arabic Language Learning for the Topic of Mubtada’ and Khabar - Rahmi, Maulida; Zulheddi, Zulheddi (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2025)
Purpose- This research aims to determine students' responses to the use of picture media and to examine the process of using picture media in learning Arabic, specifically on the topic of mubtada' and khabar, in order to facilitate students’ understanding of the material. Design/Methodology/Approach- This study employs a descriptive qualitative approach. Data were collected through observation, interviews, and documentation during the research period. The data sources include interviews with several eighth-grade students of Al-Ulum Integrated Islamic Junior High School, Medan. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. Findings- The findings indicate that students responded actively during the learning process using picture media, contributing to the achievement of learning objectives. Students were able to construct correct sentences in accordance with Arabic grammar, particularly in forming mubtada' and khabar structures, and integrating them with ism isyarah. The instructional steps implemented by the teacher using picture media were as follows: the teacher began the lesson with a standard opening, introduced the material using pictures, displayed the images, asked students to guess them, explained the correct Arabic terms related to the images, had students repeat the phrases, and concluded the lesson. Research Limitations/Implications- This research is limited to examining students' responses during Arabic learning sessions that incorporate picture media and analyzing the instructional stages used in teaching eighth-grade students at Al-Ulum Integrated Islamic Junior High School, Medan.